2013
DOI: 10.3748/wjg.v19.i25.4045
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent abdominal liposarcoma: Analysis of 19 cases and prognostic factors

Abstract: Close follow-up should be conducted in patients with RAL. Early re-operation for relapse is preferred and gross resection most likely prolongs the RFI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(31 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…18 In fact, the group of patients with liposarcoma could be divided into well-differentiated, undifferentiated, myxoid and rounded cells. Lu et al 19 showed that well-differentiated and myxoid liposarcoma patients have more prolonged survival rates than the undifferentiated variants. In our series, non-liposarcoma histology was one of the independent variables associated with worse OS and with a shorter recurrence-free period.…”
Section: Discussionmentioning
confidence: 98%
“…18 In fact, the group of patients with liposarcoma could be divided into well-differentiated, undifferentiated, myxoid and rounded cells. Lu et al 19 showed that well-differentiated and myxoid liposarcoma patients have more prolonged survival rates than the undifferentiated variants. In our series, non-liposarcoma histology was one of the independent variables associated with worse OS and with a shorter recurrence-free period.…”
Section: Discussionmentioning
confidence: 98%
“…Among high-grade dedifferentiation, they also demonstrated UPS most frequently. [13,15] Homologous dedifferentiation is the terminology proposed by the WHO, in 2013 classification, for tumors showing features of both WDLPS and PLS. [5] Earlier, these were classified as mixed liposarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Retroperitoneal/Abdominal Liposarcoma Liposarcoma is the most common mesenchymal tumor arising in the abdominal cavity, they can affect the retroperitoneum, mesentery, gastrointestinal wall, or even any organ within the abdominal cavity. [22] The most common site is the retroperitoneum, and LS represents about the 50% of all retroperitoneum sarcomas. The can present at any age, but the mean age of presentation is at 56 years, and it affects males and females equally.…”
Section: Head and Neck Liposarcomasmentioning
confidence: 99%